Fungsi Rekruitmen Politik Calon Legislatif Partai GERINDRA pada Pemilihan Umum 2019 Di Daerah Khusus Ibukota Jakarta - Aisatul Husna; Firman Manan; Ari Ganjar Herdiansah (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2019)
This study aims to determine the changes in the pattern of recruitment of Gerindra Party legislative candidates after being declared an open party in the 2019 election in DKI Jakarta and to know the function of cadre recruitment to be prepared in the Gerindra 2019 party legislative candidates in DKI Jakarta. The recruitment by the Gerindra Party is semi-open because all people who fulfill the requirements can be chosen as legislative candidates from the party. This research uses qualitative methods, with descriptive research types. Data collection through observation and interviews. 2019 elections have 20 political parties. Political parties in Indonesia are institutions that are considered important in a democratic system. Therefore, political parties are obliged to recruit candidates for legislative members who later party cadres will be placed in parliament and also through open selection both internal and external cadres. The Gerindra Party in facing the 2019 election has a policy to implement a recruitment mechanism for legislative candidates. Thus it is hoped that the best representatives of the people will be able to emerge in the 2019 elections, both at the level of the DPR RI, Provincial DPRD and City / Regency DPRD.